2010
DOI: 10.1001/archpediatrics.2010.17
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Biomarkers Predictive of Vascular Disease in a Representative Sample of US Children

Abstract: Main Outcome Measures: Body mass index; levels of C-reactive protein, homocysteine, serum and red blood cell folate, vitamin B 12 , methylmalonic acid, total cholesterol, high-density lipoprotein cholesterol, nonhigh-density lipoprotein cholesterol, triglycerides, and uric acid; and platelet count.Results: Mean values for body mass index, C-reactive protein, and homocysteine were higher in children with than without headaches, and more children with headaches were in the highest quintile of risk for these fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 44 publications
4
33
2
2
Order By: Relevance
“…Careful reading of title, abstract and full text (when available), allowed to exclude 118 articles, which did not reported original data about the epidemiological association between CRP and migraine, or did not use standardized criteria for diagnosis of migraine. Therefore, 17 clinical studies were finally included in this review, i.e., one retrospective, one interventional, 14 cross-sectional and one both interventional and cross-sectional (Table 1) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Demographical information, along with the techniques used for measuring CRP [i.e., conventional or highsensitivity (HS)], were reported, whenever available.…”
Section: Overview On Epidemiological Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Careful reading of title, abstract and full text (when available), allowed to exclude 118 articles, which did not reported original data about the epidemiological association between CRP and migraine, or did not use standardized criteria for diagnosis of migraine. Therefore, 17 clinical studies were finally included in this review, i.e., one retrospective, one interventional, 14 cross-sectional and one both interventional and cross-sectional (Table 1) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Demographical information, along with the techniques used for measuring CRP [i.e., conventional or highsensitivity (HS)], were reported, whenever available.…”
Section: Overview On Epidemiological Datamentioning
confidence: 99%
“…Nelson et al carried out a very large cross-sectional study on 11,770 children or adolescents aged 4-19 years who were enrolled in the National Health and Nutrition Survey (NHANES) in 1999 through 2004, with an overall prevalence of frequent migraine of 19.5% (2295 cases) [19]. In this large population cohort, the concentration of CRP was found to be slightly but significantly higher in cases (1.9 ± 0.1 mg/L) than in controls (1.5 ± 0.1 mg/L; p < 0.01).…”
Section: Overview On Epidemiological Datamentioning
confidence: 99%
“…Other inflammatory markers believed to be associated with vascular dysfunction are elevated in the blood of patients with migraine. It has been shown that mean values for plasma C‐reactive protein and homocysteine were higher in children with migraine than in those without headaches . In premenopausal women with migraine, particularly in those with aura, there is evidence of increased endothelial activation, a component of endothelial dysfunction, reflected by elevations in von Willebrand factor, C‐reactive protein, nitrate/nitrite, and tissue‐type plasminogen activator antigen .…”
Section: Diagnostic Molecular Markers Associated With Increased Risk mentioning
confidence: 99%
“…Available data for children are insufficient and controversial. A large US study revealed no correlation between lipid levels and the occurrence of primary headaches in children [23]. In contrast, Glueck and Bates reported a relation between severe migraine headaches and LDL cholesterol and HDL cholesterol levels in boys with primary and familial dyslipoproteinaemias [3].…”
Section: Discussionmentioning
confidence: 95%
“…However, there are only a few studies conducted in paediatric patients. Some small clinical studies showed a relation between dyslipidaemia and migraine in children [4,5]. Recent data suggest that new potential risk factors for atherosclerosis and platelet aggregation, such as brain-derived neurotrophic factor (BDNF), sCD40L (soluble CD40 ligand), serpin E1/PAI I (endothelial plasminogen activator inhibitor) and vascular endothelial growth factor (VEGF), may also play a role in the pathogenesis of atherosclerosis and platelet aggregation [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%